A comparative evaluation of calix[4]arene-1, 3-crown-6 as a ligand for selected divalent cations of radiopharmaceutical interest. Issue 55 (10th October 2019) - Bauer, David; Blumberg, Markus; Köckerling, Martin; Mamat, Constantin
Abstract : The stability constants of the promising ligand calix[4]arene-1, 3-crown-6 and divalent metals of radiopharmaceutical interest: lead, barium, and strontium, were determined via NMR and UV/Vis techniques. Abstract : Metals, which form divalent cations, including the alkaline earth metals offer radionuclides like lead-203, lead-212, barium-131, and strontium-89, which are promising candidates for radiopharmaceutical applications. Besides, the heavy homologous nuclides radium-223 and radium-224 – with similar properties to barium – are suitable alpha-emitters for targeted alpha-particle therapy. However, there is a lack of suitable chelation agents, especially for heavy group 2 metals. The macrocycle calix[4]arene-1, 3-crown-6 seems to interact with these metals strongly. Therefore, this ligand and its coordination to the divalent cations of barium, strontium, and lead have been investigated. The complex formation was analyzed by NMR and UV/Vis titration experiments in acetonitrile, and stability constants were determined to be >4 with both methods. It was found that the stability of these complexes increase in the order strontium, barium, and lead. Additional to these investigations, X-ray crystallography, solvent-dependent 1 H NMR, and 207 Pb NMR measurements were performed to deliver deeper insight into the coordination chemistry of this ligand.